Aves de rapina da mata do Alto Uruguai - Meller, Dante Andres (2014)
As top predators birds of prey are excellent bioindicators for any environment. The community is divided into four orders (Cathartiformes, Accipitriformes, Falconiformes and Strigiformes), presenting great diversity of species. Many disappear with ecosystems changes, and habitat loss is the main cause of extinctions. South America is the continent with the greatest richness of raptors, and only in Brazil 98 species have been recorded. The degradation of some biomas, however, has caused the local extinction of raptors with great ecological requirements. The Atlantic Forest, which has bit more than 10% of its forest cover still preserved, has suffered along almost its entire length the loss of some species which are very sensible to human impacts, such as Harpia harpyja and Morphnus guianensis. In the northwestern region of Rio Grande do Sul, forest loss was significant and with it much of the fauna that originally inhabited the area. Given protected area establishments and connection with the extensive forests of Misiones (Argentina), some places still have many raptors rare or regionally endangered. It is the case of Turvo State Park ( Parque Estadual do Turvo - PET) and the Indigenous Land of Guarita ( Terra Indígena do Guarita - TIG), which are distant only 15 km, in a fragmented landscape, with forest patches under different attributes and different mosaics. In this context we sought to identify how the community of raptors responds to the factors presented in the fragments under different conditions. Through specific methodology for diurnal raptors we also sampled the situation of the community in TIG. Fourteen fragments and seven points were sampled in the TIG. The data of TIG were compared to those found in a survey with the same methodology in PET. The results showed the only factor that influences the richness and the frequency of occurrence of raptors in the fragments is the area. Factors as isolation (distance between a fragment and PET or TIG), quantity of forest cover in the mosaic and the form of the fragment were not significant. This is probably given by the great capacity of dispersion of birds of prey, differing from others groups of fauna. The raptors community of TIG presented very similar results to that found in PET. We emphasize some inedited and conservation relevance records for TIG, such as Sarcoramphus papa, Leptodon cayanensis and Spizaetus melanoleucus. Even if TIG is in a context less favorable to conservation when compared to PET, our results shows the importance of the indigenous area for the conservation of the raptors of the region. Once raptors require large areas, are territorial, move easily and have an aversion to disturbances, large fragments offers better conditions of surviving than small ones, especially for species with larger ecological needs. Thus, strategies that involve the preservation of large forest fragments in the northwestern region are fundamental for the preservation of the community of birds of prey of the Alto Uruguay Forest.